Sistem Penentu Estimasi Biaya Proyek Pengembangan Perangkat Lunak Menggunakan Metode COCOMO II - Harsono, Eko Febri; Sukmaaji, Anjik; Widodo, Arifin Puji (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
Estimated cost of the software project is very important for the government before the project tendered. The government must determine the HPS (Harga Perkiraan Sendiri) by surveying the price of the project in each region. Because there is no specific regulation related to the HPS itself in the presidential regulation. Perpres No. 70 of 2012 explains that HPS is only for the procurement of goods or services and there are no specific regulations related to HPS for software projects. Therefore, the government has difficulty determining the estimated total value of software development projects. based on these problems, the application of determining the cost of a software development project was built using the COCOMO II method. The application built can determine the estimated total value of a software development project using the COCOMO II method before the project is tendered. So the government is easy to determine the HPS in each software development project.